Social services for elderly persons - Dimitrijoska, Suncica; Trbojevik, Svetlana; Ilievski, Vladimir (Ревија за социјална политика/Journal of Social Policy, 2019)
The ongoing demographicchanges such as an increase of number of elderly persons, extension of the life expectancy, impose specific requirements in the area ofsocial protection.Fulfilment of elderly people needs requires additional financial resources for their social and financial security, health protection, communication and social engagement. The analysis of services for the elderly involves a wide range in grouping such as: services for information and referral, professional assistanceand support, counselling services, services at home, services in community and out- of-home services. Social services that are intended for the elderly are designed to maintain the autonomyand independentliving of elderly in order for them to be independent from the system that is providing social services.